Preliminary study on bio-film formation in various conditions - Nekmat, Ahmad Zaki (2018)
Bio-film is a group of microorganisms that stick to each other and bind to surface. The bio-film mostly can be found in the wet and damp area. The research is focus on the effect of type of surface, range of temperature and types of water source to the growth of the bio-film. This study used material in forms of containers, various source of water collected in location near UMK Jeli campus and 2 ranges of growth temperature under controlled environment. The difference of parameters were affected the final results of the bio-film growth. The final result was measured using the weight measuring technique and optical density of the samples. From all the samples tested, the sample with source of water from sewage, the temperature of 30°C and polystyrene material has the highest Bio-film growth. The result also indicates that Bio-film growth project needed specific method to gained more accurate data.